Euler–Lagrange modeling of wood chip gasification in a small-scale gasifier. Issue 3 (August 2015) - Hu, Guilin; Li, Guoneng; Zheng, Youqu; Zhang, Zhiguo; Xu, Yousheng
Abstract: The mathematical model for physical and chemical processes during wood chips gasification in a gasifier is presented in this paper to offer some reference data for the gasifier structure design and operation optimization. The RNG k – ε model is employed in the numerical simulation of turbulent combustion gas flow. Non-premixed combustion model is used to describe the species reaction and transportation. The movement and gasification of wood chip particle is described by Lagrange model. The Eulerian conservation equations of gas phase are solved using the control volume approach. The distributions of temperature and chemical species, residence time of wood particles are numerically obtained. The results indicate that this design will cause vortex structure at lower chamber for the interaction between the forwarding flow of air and the reverse flow of syngas. This vortex will make produced syngas to combust further; the productions are CO2 and H2 O substituting CO and H2, which will decrease the temperature inside the chamber and quality of syngas. In order to optimize operational case, five different equivalence ratios of airflow are computed and compared with experimental test. The predicted temperatures of outgoing gas agree well with the experimental results. Modeling results can provide some references for gasifier structure design and optimum operation case.